PARTISIPASI STAKEHOLDERS DALAM OPERASI DAN PEMELIHARAAN JARINGAN IRIGASI PADA DAERAH IRIGASI UNDA DI KABUPATEN KLUNGKUNG - Ari Wahyudhi, I Made; Norken, I N.; Suputra, I Ketut (JURNAL SPEKTRAN, 2015)
Although it has a large amount water resources but the agricultural land of Unda Irrigation Area still has water crisis. Many potential water of  Unda river waste into the sea that indicate the management of irrigation network is still less. The lack participation of stakeholders from the government and the public in this case Irrigation Area of Unda river seen from the number of the irrigation channels damage and existing buildings. The approach used in this research is explorative and descriptive approach. The collecting Data obtained by questionnaires and in-depth interviews with stakeholders were selected using purposive sampling method. Data were analyzed with descriptive qualitative Likert scale used to measure attitudes, opinions and perceptions of stakeholders in the securement and maintenance. The test results show the value of the adjusted R Square is 0.747. This mean that stakeholders have 74.7% effects, while 25.3% is influenced by other factors. Which is government contributes most, followed by Subak / P3A. It caused by the influence of the test simultaneously or partial value of Fcount > Ftable, so it can be concluded participation of stakeholders have a significant influence on this operation and maintenance of irrigation system in Unda Irrigation area in Klungkung district either simultaneously or partially. This means increased participation of stakeholders simultaneously and partially will improve the operation and maintenance of irrigation networks. From this research can be given some suggestions. In order for the participation of stakeholders can be improved, the other stakeholders instead of government sector and Subak / P3A which is not included in the study need to observe. To increase the participation of Subak / P3A in the operation and maintenance of irrigation networks needs to be disseminated about the importance of stakeholder participation by the government so that the participation of Subak / P3A can be maximized.
Keywords: Participation of stakeholders, Operation and Maintenance of Irrigation System, Goverment, subak